Head-to-head: football vs. ice hockey as national sport in Sweden - Stark, T.; Andersson, T. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
This article examines the cultural and economic characteristics, as well as the historical trends, of Swedish football and ice hockey, two of the country`s national sports. Utilizing Arjun Appadurai`s theory of globalization flows (scapes), the historical development of these sports from the early twentieth century to the present is analyzed. The study highlights how football and ice hockey have been shaped by ideological, media, technological, and economic factors, as well as their relationships with audiences and supporter cultures. The findings reveal that football, with its grassroots development and club-based organization, contrasts with ice hockey`s more nationalized structure and top-down development, heavily influenced by North America. During the 1980s, ice hockey surpassed football in economic, media, and audience aspects, and soon also technologically. However, through a robust supporter culture, football regained strength in the 2000s, leading to a growing cultural divergence between the two sports. The future appears bright for both, but football seems to have a greater economic potential, due to revenue generated from player transfers and participation in European tournaments.